Rola chrześcijańskiej myśli filozoficznej i teologicznej w procesie rodzenia się nauki nowożytnej = The role of christian philosophical and theological thought in the process of conception of modern thought - Wielgus, Stanisław (1939- ) (Zielona Góra: Uniwersytet Zielonogórski)
The author proves that the philosophy and theology of the Middle Ages played a crucial role in the creation and development of modern thought and in the crystallisation of modern society.
Keywords: chrześcijaństwo; filozofia; teologia; nauka